Influence of passive, diet-based, hydration on muscle quantity assessment - Viken, Julian Seiler; Nettum, Vebjørn; Paulsen, Gøran; Seynnes, Olivier (Frontiers in Physiology, 2025)
BackgroundThis study investigated the impact of passive changes in hydration level on measurements of lean tissue mass (LTM) and muscle morphology.MethodsSixteen healthy participants (13 males, 3 females) completed two testing sessions 24 h apart, including dual-energy X-ray absorptiometry (DXA), 3D ultrasound imaging of the vastus lateralis (VL), and bioelectrical impedance analysis (BIA). Participants fasted for 12 h before each session. Hydration was manipulated by assigning participants randomly to either a non-hydrated state, abstaining from fluids until testing, or a hydrated state, consuming water equal to 1.5% of body mass 2 hours prior.ResultsTotal body water, measured using bioelectrical impedance analysis (BIA), was lower in the non-hydrated condition (48.6 ± 9.7 kg) than in the hydrated condition (49.0 ± 9.8 kg, p = 0.015). In the hydrated condition, total LTM, measured using DXA, was higher for the full body (60.8 ± 11.8 kg vs. 60.0 ± 11.9 kg, p < 0.001) and the trunk (29.2 ± 5.3 kg vs. 28.6 ± 5.4 kg, p < 0.001). Hydration did not significantly affect LTM in the upper (p = 0.251) or lower limbs (p = 0.298), or the thigh (p = 0.051). Volume (p = 0.105) and cross-sectional area (CSA; p = 0.114) of the VL were also unaffected.ConclusionSmall changes in hydration levels induced passively under temperate conditions may not significantly affect measurements of muscle morphology or limb measurements of LTM. However, monitoring changes in muscle quantity with total LTM may be biased by water intake and trunk hydration if these factors are not controlled. Caution is warranted (e.g., standardisation) when using total LTM to monitor changes in muscle quantity.